IMPLEMENTATION NATIONAL AGREEMENTS IN THE DIVISION OF COLLECTIVE PROPERTY IN THE TIME OF DIVORCE - Yulius Oktaber (Faculty of Law, Universitas Lampung, 2023)
This research was conducted to find out the agreement made by the husband and wife before the marriage takes place which is called the marriage agreement or prenuptial agreement which regulates the separation of assets. The joint assets that are formed in marriage are from the time the marriage takes place until the date the marriage bond is broken. Furthermore, based on Article 38 of Law no. 16 of 2019 stipulates that marriages can be dissolved due to: death; divorce; and by court decision. This study uses the Normative Juridical legal research method, whose approach is carried out by examining statutory regulations that can be used as a legal reference in the application of Prenuptial agreements and analyzing the judge's decision at the Bandar Lampung Religious High Court Number: 0004/Pdt.G/2021/PTA.Bdl dated January 27, 2021 as a guideline for sharing joint assets after divorce. The results of this study are that there is a legal position in the settlement of the distribution of joint assets after divorce and shows that the legal position in the settlement of the distribution of joint assets after marriage has been regulated in marriage law and the compilation of Islamic law. Furthermore, the judge's consideration regarding the distribution of joint assets in the Religious Court Decision No.0004/Pdt.G/2021/PTA.Bdl. regarding the divorce decision.